The internal conflicts and contemporary dilemmas of America’s national characteristics - Shaoqing Zhou (International Journal of Anthropology and Ethnology)
Abstract Since the twenty-first century, the political landscape of the United States has undergone dramatic changes. One of the key manifestations is the rise of evangelical Christian nationalism and its significant internal and external political consequences. While the causes behind the rise of evangelical Christian nationalism in the United States and its resulting political effects are multifaceted, fundamentally, these developments are closely linked to issues that have existed throughout the history of the American nation-building process, such as the ambiguity of national objectives and the conflict of value systems. The root cause lies in the instability and multifaceted nature of the American national characteristics. Since its founding, the U.S. has consistently wavered in its national characteristics, presenting three competing models of the modern American state: the empire of liberty, the liberal civic state, and the Anglo-Saxon Protestant nation. The positioning of these three national characteristics, which are seemingly contradictory yet often coexisting, has, on the one hand, shaped the unique character of the United States, while on the other hand, it has exposed the U.S. to periodic conflicts and crises. It is important to note that the rise of evangelical Christian nationalism in the twenty-first century, coupled with the increasing polarization of American politics, may disrupt the previously existing balance of conflicting yet coexisting national identities. With the continuous decline in the population of the white majority, this balance is likely to break down further, potentially resulting in prolonged internal strife within the U.S.